Proposal and performance comparison of various solar-driven novel combined cooling, heating and power system topologies - Saini P.; Singh J.; Sarkar J. (My University, 2025)
In the present research work, three novel topologies (Configuration-1, Configuration-2 and Configuration-3) of solar energy driven combined cooling, heating and power (CCHP) system are proposed to identify eco-friendly system for future energy demand and human comfort. The proposed CCHP systems consist of solar thermal evacuated U-tube collector, organic Rankine cycle for power, ejector refrigeration cycle for cooling and heat exchanger for heating. Through theoretical analysis, the thermodynamic (energy and exergy) performances of all three configurations are investigated by utilizing solar energy and compared by estimating the objective functions like performance index, irreversibility, exergy efficiency, net work output, heating output, entrainment ratio and cooling output. The objective functions are analyzed on the basis of generator temperature, evaporator temperature, condenser temperature and solar intensity as decision variables. The practical feasibility of the proposed systems is discussed as well. It is revealed that configuration-1 has maximum overall exergy efficiency and power output while configuration-3 has maximum performance index and heating output as compared to other configurations. Configuration-2 has maximum cooling output as compared to other configurations. In overall, Configuration-3 is best considering higher energy performance, lower number of components (compactness), wider operating range and energy demand flexibility while other configurations also have their merits. © 2019 Elsevier Ltd